PENANGANAN PASCA TANGKAP HASIL PERIKANAN DI NEGERI WAAI KECAMATAN SALAHUTU KABUPATEN MALUKU TENGAH - Nendissa, Desire M; Kaya, Adrianus O W; Rieuwpassa, Fredrik; Loppies, Cindy R M; Lokollo, Edir (Balobe: Jurnal Pengabdian Masyarakat, 2023)
Waai Vilage is one of the of fresh fish producers located in Salahutu District, Maluku Tengah Regency. The availability of fresh fish for community needs is an important factor that must be fulfill by fishermen and seller so that an understanding of handling fish is very importance when it’s caught to the hands of consumers remains at a good and prime level of freshness. The importance of post-capture handling fish will have a positive impact on fishermen, seller and consumers because it will provide value added to the fish, the selling value will be higher, the nutrition of the fish caught will also be maintained so that it will affect further processed products.